The interplay between students’ home literacy environment, reading attitudes and comprehension: a serial mediation analysis using PIRLS 2021-data - Renée Claes; Jana Laga; Katrijn Denies; Nele Bleukx; Jonas Dockx; Hilde Van Keer; Koen Aesaert (Large-scale Assessments in Education)
Abstract Background Providing a rich home literacy environment (HLE) is considered to contribute to the development of students’ reading comprehension. However, less research attention has been given to the underlying mechanisms that influence this relationship, including potential mediating characteristics. The present study aims to assess whether students’ reading enjoyment, reading motivation and reading frequency mediate different aspects of the active and passive HLE and reading comprehension of Grade 4 students in Flanders (Belgium). Methods This study uses the Flemish data of the Progress in International Reading Literacy Study (PIRLS) 2021. Participants were 5114 students from 141 schools and their parents. The hypotheses were tested using a serial mediation model implemented through structural equation modelling. Results We observed different associations between specific aspects of the HLE and fourth graders’ reading comprehension. Both an active reading climate and the amount of books at home were found to be positively associated with students’ reading comprehension. We found no contributions of parents’ reading enjoyment and their own reading frequency to their child’s reading comprehension. We found significant indirect effects of both the active reading climate and parents' reading enjoyment on students' reading comprehension, mediated through students' reading enjoyment, motivation and reading frequency. Additionally, we found evidence for an indirect pathway from the amount of books at home to students' reading comprehension, mediated by their reading frequency. Conclusions Our findings highlight the importance of conceptualizing HLE as a broad construct consisting of multiple components (e.g., activities, beliefs, availability of literacy-related resources at home), as these aspects are related to students’ reading comprehension development in different ways.